Heteronormative higher education: Challenging this status quo through LGBTIQ awareness-raising - Matthyse, G. (South African Journal of Higher Education, 2017)
This paper focus on the challenges homophobia and transphobia pose to LGBTIQ students at the University of the Western Cape (UWC), a historically black peri-urban university located on the margins of Cape Town. Both the geographical location as well as the internal environment of the university give rise to various challenges for LGBTIQ identifying, and particularly gender non-conforming, students around their sexual freedom and self-affirmation. In transcending the vacuum between the challenges faced by these students and the existing human rights discourse on non-normative sexual orientations and gender identities, the Gender Equity Unit, through its student-driven LGBTIQ programme LoudEnuf, its support staff and in collaboration with the student structure GaylaUWC has been educating and sensitising the campus community through its intersectional awareness-raising initiatives. This paper focuses on the effectiveness of awareness-raising in creating a welcoming, comfortable, liberating and safe campus for LGBTIQ students to access comprehensive quality education.